Osmotic regulation of rpoS-dependent genes in Escherichia coli. - Hengge-Aronis, R (1993)
The rpoS gene, which encodes a putative alternative sigma factor (sigma S), is essential for the expression of a variety of stationary-phase-induced genes as well as for stationary-phase-specific multiple-stress resistance. As previously shown for the otsA and otsB genes (R. Hengge-Aronis, W. Klein, R. Lange, M. Rimmele, and W. Boos, J. Bacteriol. 173:7918-7924, 1991), we demonstrate here that additional rpoS-controlled genes (bolA, csi-5) as well as at least 18 proteins on two-dimensional O'Farrell gels could be induced in growing cells by osmotic upshift via an rpoS-dependent mechanism. Also, rpoS-dependent thermotolerance and resistance against hydrogen peroxide could be osmotically stimulated. In contrast, the expression of glgS, while exhibiting strong stationary-phase induction, was only weakly increased by elevated osmolarity, and several rpoS-dependent proteins previously identified on two-dimensional gels were not osmotically induced. During osmotic induction of rpoS-dependent genes, rpoS transcription and the level of sigma S remained unchanged. We conclude that osmotically regulated genes represent a subfamily within the rpoS regulon that requires differential regulation in addition to that provided by sigma S.